(untitled) (Conferencea, 2024)
In the article, the changes in quality indicators, the influence of equipment parameters, the factors affecting the efficiency of cotton transportation in pneumatic transport and their optimization as a result of exposure of cotton raw materials to the working parts of pneumatic transport equipment at the cotton ginning enterprise were studied. Advantages and disadvantages of existing cotton separators in India and Uzbekistan were presented.